Effectiveness of virtual postpartum education classes on maternal knowledge and health-seeking behavior in Kupang City: a pre-post study - Ignasensia Dua Mirong; Dewa Ayu Putu Mariana Kencanawati; Odi L. Namangdjabar; Hasri Yulianti; Martina Fenansia Diaz; Diyan Maria Kristin (International Journal of Public Health Science (IJPHS), 2026)
Postpartum maternal health services are routinely administered to postpartum mothers four times daily. In reaction to the COVID-19 pandemic, modifications have transpired in healthcare services, encompassing postpartum maternal health. Virtual homecare services facilitate remote interaction with patients without utilizing healthcare services. This study aims to assess the impact of virtual postpartum maternal classes on knowledge, early detection skills, and treatment-seeking behaviors. This study employs a quantitative methodology utilizing a quasi-experimental pretest-posttest design. A virtual postpartum mothers’ class program was conducted every two weeks for three months. The total population consists of 109 individuals, while the purposive sample comprises 32 individuals. Data acquisition through questionnaires (pre-tests and post-tests). Conduct an analysis of the data utilizing the Wilcoxon signed ranks test. The study's findings demonstrate a substantial impact of virtual postpartum mother class mentoring on knowledge levels (p = 0.000), early detection of complications by postpartum mothers (p = 0.001), and treatment-seeking behavior (p = 0.001). The introduction of virtual postpartum maternal classes significantly enhances postpartum mothers' knowledge, their capacity to identify postpartum complications, and their propensity to seek treatment.